Application of a high resolution distributed temperature sensor in a physical model reproducing subsurface water flow. (February 2017) - Bersan, Silvia; Schenato, Luca; Rajendran, Aneesh; Palmieri, Luca; Cola, Simonetta; Pasuto, Alessandro; Simonini, Paolo
Abstract: A distributed temperature optical fiber sensor system with a sub-centimeter spatial resolution has been incorporated in a sand-box model at the aim of investigating the variations induced by internal erosion on the temperature distribution in a dike. In particular, the laboratory investigation aims at studying the spatial distribution of the temperature variations occurring in the surroundings of an erosion channel ( pipe ). The calibration of the setup consisted in measuring the thermal response of an intact sample to a horizontal flow, with the inflowing water maintained at a constant temperature higher than the room temperature. No erosion occurred in the calibration test. The results of the calibration are presented in this paper and show that with the sensing system adopted temperature mapping in a soil sample can be obtained with such a richness of detail which is not comparable with that achieved adopting a system of pointwise sensors.